Dating of Stratified Settlement Remains in Faid Pilgrim Station, Northwest of Saudi Arabia - Nassr, Ahmed; Elhassan, Ahmed; al-Hajj, Mohammed; Tueaiman , Ali (Journal of Islamic Archaeology, 2023)
Faid was a major pilgrim Islamic oasis located 120 km southeast of the Ha’il Province, northwest of Saudi Arabia. It was founded on the major Hajj Road between Baghdad/Kufa and Medina and was developed by Zubaydah bint Ja’far, granddaughter to the Caliph Abu Ja’far al-Mansur (the founder of Baghdad) and wife to the fifth Abbasid Caliph, Harun Ar-Rašid 775–785 CE. Therefore, during the reign of Harun Ar-Rašid Caliph, the major pilgrim road was renamed from Darb Heerah to Darb Zubaydah. The archaeological site in Faid was referenced and described by several travellers and scholars and excavated by the Heritage Commission, Ministry of Culture, Saudi Arabia 1998–2012. From 2014–2022, the University of Ha’il conducted nine fieldwork seasons at the site. The authors directed the last four seasons, which revealed numerous new discoveries from stratified excavations. This study aims to reconstruct the occupation chronology at the site based on stratigraphic contexts and supported by radiocarbon dating, artefact studies, and written resources. Three occupation horizons were identified at the site; the early Abbasid period was the dominant occupation. The resulting radiocarbon calibrated ages were consistent with the preliminary archaeological studies carried out by the authors. The results presented in this paper represent an attempt to reconstruct the chronology of the study site.